The cost of return to play protocols in collegiate athletes recovering from coronavirus disease 2019 - Macnamara, J. P.; McCoy, C. W.; Hendren, N. S.; Tietze, D. C.; Milburn, N. K.; Dabas, N.; Mitrani, R. D.; Goldberger, J. J.; Kirk, K. M.; Shah, J. P.; Best, T. M.; Levine, B. D. (Medicine & Science in Sports & Exercise, 2022)
Introduction/Purpose SARS-CoV-2 infection (COVID-19) can result in myocarditis. Protocols were developed to allow competitive athletes to safely return to play (RTP) after a COVID-19 infection, but the financial impact of these protocols is unknown. Our objective was to determine the differential cost of post-COVID-19 RTP protocols for competitive collegiate athletes.